MAPPING OF ALFAMART AND INDOMARET DISTRIBUTION IN THE MEDOKAN SEMAMPIR AND SEMOLOWARU SUB-DISTRICT AREA USING GOOGLE MYMAPS - Arga Erditya Herdirinanda; Hendrata Wibisana (CI-TECH, 2021)
Indonesia is a country that has a high population density. The increasing population causes an increase in the demand for household needs. As time goes by, human needs are increasing day by day. Starting from primary needs to secondary needs. The city of Surabaya is the second largest metropolitan city after Jakarta with a population of around 2,874,314 people in 2020. With such a large number, of course, it has various kinds of demands to fulfill primary needs, Alfamart and Indomaret as the two largest retail companies in Indonesia are trying to be in the midst of Public. However, the uneven distribution of Alfamart and Indomaret locations causes the public to be often confused about their existence. To meet the need for information dissemination in that location, the system will be made based on mobile web so that the system can be accessed via a mobile smartphone device that is equipped with a GPS (Global Positioning System) so that it can find out the coordinates of the location of Alfamart and Indomaret, namely in the form of latitude and longitude data. This will make it easier for people who want to know the location and know the distance to the intended location and data by utilizing services from Open Camera and Google Maps.